Inmigración y subalternidad en el cine argentino: Nobleza Gaucha - Pablo Alvira; Ronen Man (Les Cahiers ALHIM)
In the early twentieth century, the fear of cosmopolitan immigration crowd, led to a large number of Argentine intellectuals and politicians to consider the need to create a sense of belonging to the nation, to build an Argentine identity that allows to "nationalize" the immigrant conglomerate. Most of the artistic and cultural expressions of the period were functional to this project of the dominant class, including cinema, which revealed as an ideal vehicle for the configuration of this collective imaginary, excluded the social criticism and omitted the presence of the subaltern classes. But, in the decade after the Centennial of the Revolution of May of 1810, appeared a series of films that gave visibility to both the political and social problems, and the subaltern groups. This paper discusses Nobleza Gaucha, the first film in those series, emphasizing its representation of subaltern groups, immigrants and natives, which involves considering its particular reinterpretation of “criollismo” and its quest for realism, defiantly for hegemonic discourses.